A directional lamination cell for adapting a single-sided dry-method positive electrode sodium-ion battery and a preparation method thereof

CN123018159APending Publication Date: 2026-10-30广东兆瑞新能源技术有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611374561.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

本发明通过多层梯度干法正极活性层的设计,能够优化单面干法正极的界面结构,协同改善电池的循环稳定性,并且无需新增设备、可直接利用现有叠片工装的定向排布叠片电芯结构,解决现有单面干法正极叠片过程中裸铝箔腐蚀、电芯微短路、容量衰减的技术问题

Benefits of technology

本发明提供的钠离子电池定向叠片电芯,直接适配现阶段量产成熟的单面干法正极工艺,且叠片排布规则完全兼容现有叠片工装、焊接、封装设备,无需设备改造,可快速实现批量样品制备与性能验证,降低研发与量产成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application belongs to the technical field of sodium ion battery manufacturing, and particularly relates to a sodium ion battery directional laminated cell suitable for single-side dry-method positive electrode and a preparation method. The sodium ion battery directional laminated cell comprises a plurality of alternately stacked positive electrode sheets and negative electrode sheets and a separator arranged between adjacent positive electrode sheets and negative electrode sheets; the positive electrode sheet is a single-side dry-method positive electrode sheet; the negative electrode sheet is a double-side dry-method negative electrode sheet; the single-side dry-method positive electrode sheet comprises an aluminum foil current collector; a plurality of gradient dry-method positive electrode active layers are arranged on one side surface of the aluminum foil current collector, and the gradient dry-method positive electrode active layers form a gradient structure with a porosity gradually increasing and an active material content gradually decreasing layer by layer in a direction away from the aluminum foil current collector. Through the design of the plurality of gradient dry-method positive electrode active layers, the interface structure of the single-side dry-method positive electrode can be optimized, the cycle stability of the battery can be improved, and the technical problems of bare aluminum foil corrosion, cell micro-short circuit and capacity attenuation in the existing single-side dry-method positive electrode lamination process can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sodium-ion battery manufacturing technology, specifically relating to a sodium-ion battery oriented stacked cell adapted to a single-sided dry cathode and its preparation method, which is suitable for the large-scale assembly and performance optimization of sodium-ion battery cells prepared by dry electrode process. Background Technology

[0002] Sodium-ion batteries, with their advantages of abundant resources, low cost, and high safety, have become a core candidate technology in the fields of large-scale energy storage and low-speed power batteries. However, sodium-ion battery cathode materials, such as polyanionic sodium iron pyrophosphate (NFPP), Prussian blue analogues (PB), and layered oxides, are highly sensitive to moisture. They are prone to side reactions when exposed to water, directly causing problems such as battery capacity decay, increased internal resistance, and shortened cycle life.

[0003] Currently, traditional wet electrode processes for sodium-ion battery cathode materials require the use of large amounts of organic solvents and high-temperature baking and drying after coating, which easily leads to water absorption, cracking, and interface degradation of the cathode material. Dry electrode processes, on the other hand, eliminate the need for organic solvents and high-temperature baking, effectively avoiding the water absorption failure problem of sodium-ion battery cathode materials. This makes it an ideal technical route for sodium-ion battery cathode preparation and it has been widely researched and applied in the battery field. However, current dry electrode processes still face technical bottlenecks. Limited by the precision of film-forming equipment and the maturity of the process, sodium-ion battery cathodes can only achieve stable single-sided dry coating of aluminum foil. Double-sided coating easily leads to uneven porosity, compaction density, and water content on both sides, severely affecting battery consistency and cycle stability. Therefore, the mainstream mass-produced and R&D cathodes in the industry are all single-sided dry-coated structures.

[0004] Existing single-sided electrode stacking technologies still suffer from significant compatibility defects. Patent application number 2010202464614 discloses a power-type lithium-ion battery cell where both positive and negative electrodes are single-sided coated, with the coating layers facing each other and a separator sandwiched in between, then folded in an S-shape. This existing solution aims to address the problem of poor battery consistency caused by large thickness errors in double-sided coatings. It requires both the positive and negative electrodes to be single-sided coated with opposite coating surfaces, representing a symmetrical arrangement. This is only suitable for symmetrical electrode scenarios in lithium-ion batteries and cannot adapt to the asymmetric process constraints of existing sodium-ion batteries with single-sided positive electrode coating and double-sided negative electrode coating. If conventional single-sided dry-process positive electrodes are directly applied to traditional interleaved stacking processes, the bare aluminum foil of the positive electrode will directly contact the active layer of the negative electrode and the electrolyte. Residual alkaline substances such as NaOH and Na2CO3 on the surface of the sodium-ion positive electrode will corrode the aluminum foil in the electrolyte system, generating high-resistivity products such as AlF3 and Al2O3, causing a continuous increase in the battery's DC internal resistance (DCR) and rapid capacity decay. Meanwhile, the potential difference between the bare aluminum foil and the negative electrode can easily cause sodium deposition and micro-short circuits in the cell, leading to a decrease in battery safety.

[0005] In summary, existing stacking processes are all based on the design logic of symmetrical arrangement of positive and negative electrode sheets, which cannot adapt to the special process constraints of dry-process single-sided cathodes. The industry currently lacks cell structures and fabrication processes that do not require additional equipment, are compatible with existing tooling, and can effectively solve the problems of aluminum corrosion and micro-short circuits in single-sided dry-process cathodes. This severely restricts the performance verification and large-scale application of dry-process sodium cathodes. Furthermore, conventional dry-process cathode films have a single, uniform pore structure, which suffers from high ion transport resistance near the current collector and insufficient conductivity of the surface active material. Electronic conductivity and ion transport capacity cannot be optimized synergistically, making it difficult to balance battery energy density and cycle performance.

[0006] Therefore, there is an urgent need for a technical solution that can achieve the assembly of single-sided dry sodium cathode full cells using existing stacking tooling without increasing equipment modification costs. Summary of the Invention

[0007] To overcome the shortcomings of existing technologies, the purpose of this invention is to provide a sodium-ion battery oriented stacked cell adapted to a single-sided dry cathode and its preparation method. This invention optimizes the interface structure of the single-sided dry cathode by designing a multi-layer gradient dry cathode active layer, synergistically improving the cycle stability of the battery. Furthermore, it eliminates the need for additional equipment and can directly utilize the oriented stacked cell structure of existing stacking tooling, solving the technical problems of bare aluminum foil corrosion, cell micro-short circuits, and capacity decay during the stacking process of existing single-sided dry cathodes.

[0008] To achieve the above objectives, a first aspect of the present invention provides a sodium-ion battery oriented stacked cell adapted to a single-sided dry-process positive electrode, comprising a plurality of alternately stacked positive and negative electrode sheets, and a separator disposed between adjacent positive and negative electrode sheets. The positive electrode is a single-sided dry-process positive electrode; the negative electrode is a double-sided dry-process negative electrode; the single-sided dry-process positive electrode includes an aluminum foil current collector; one side of the aluminum foil current collector is provided with a multi-layer gradient dry-process positive electrode active layer, and the other side is an exposed aluminum foil surface; the multi-layer gradient dry-process positive electrode active layer is sequentially stacked with a first positive electrode film layer, a second positive electrode film layer, and a third positive electrode film layer along the direction away from the aluminum foil current collector, forming a gradient structure in which the porosity increases layer by layer and the content of active material decreases layer by layer; The first positive electrode membrane layer has a porosity of 15%~25% and a positive electrode active material content of 95%~97%; the second positive electrode membrane layer has a porosity of 25%~35% and a positive electrode active material content of 91%~93%; the third positive electrode membrane layer has a porosity of 35%~50% and a positive electrode active material content of 87%~89%. The positive electrode plates are arranged in a uniform orientation inside the cell, that is, the multi-layer gradient dry positive electrode active layer faces the negative electrode plate, and the exposed aluminum foil faces outward.

[0009] Preferably, the total thickness of the multilayer gradient dry positive electrode active layer is 60~140μm; the thickness of the first positive electrode film layer is 20~50μm; the thickness of the second positive electrode film layer is 30~60μm; and the thickness of the third positive electrode film layer is 10~30μm.

[0010] Preferably, the positive electrode active material in the multilayer gradient dry positive electrode active layer is at least one of sodium iron pyrophosphate, Prussian blue analogue, and layered oxide, more preferably sodium iron pyrophosphate.

[0011] Preferably, the double-sided dry negative electrode includes an aluminum foil current collector and negative electrode active layers disposed on both sides of the aluminum foil current collector; the negative electrode active material in the negative electrode active layer is hard carbon; the double-sided dry negative electrode only has the negative electrode active layer facing the multilayer gradient dry positive electrode active layer participating in the electrochemical reaction, and the negative electrode active layer on the other side is a capacity redundancy sodium replenishment reserve layer.

[0012] Preferably, the directional arrangement cycle unit of the sodium-ion battery oriented stacked cell is: exposed aluminum foil surface - multi-layer gradient dry-process positive electrode active layer || separator || negative electrode active layer - aluminum foil - negative electrode active layer || separator || multi-layer gradient dry-process positive electrode active layer - exposed aluminum foil surface; the number of positive electrode sheets is one more than the number of negative electrode sheets. In this invention, between adjacent positive and negative electrodes, only the coating surface of the positive electrode and the coating surface of the negative electrode are opposite each other and electrochemically paired through the separator. The exposed aluminum foil surface of the positive electrode only contacts the separator and does not form an opposition with any negative electrode active layer.

[0013] Preferably, during the stacking of the sodium-ion battery oriented stacked cells, precise positioning is achieved through a limiting fixture, preventing the bare aluminum surface from contacting the negative electrode due to electrode misalignment, which helps to significantly reduce the risk of micro-short circuits and self-discharge.

[0014] Preferably, the single-sided dry cathode sheet undergoes pre-sodium treatment.

[0015] A second aspect of the present invention provides a method for preparing a sodium-ion battery oriented stacked cell adapted to a single-sided dry-process cathode, for preparing the above-mentioned sodium-ion battery oriented stacked cell, comprising the following steps: S1. The positive electrode active material, conductive agent, and polytetrafluoroethylene are dry-mixed at a mass ratio of 86~97:1.5~10:1.5~10, and then subjected to high-speed shearing to obtain positive electrode fibrous powders with different proportions. The fibrous powders with different proportions are taken in batches and layered by roller pressing to prepare the first positive electrode film layer, the second positive electrode film layer, and the third positive electrode film layer in sequence, forming a gradient dry positive electrode film. The gradient dry positive electrode film is placed on one side of the aluminum foil current collector and then hot-rolled to obtain a single-sided dry positive electrode sheet. S2. The negative electrode active material, conductive agent, and polytetrafluoroethylene are dry-mixed according to the mass ratio, and then subjected to high-speed shearing to obtain negative electrode fibrous powder; the negative electrode fibrous powder is rolled to obtain a negative electrode film layer; the negative electrode film layer is attached to both sides of the aluminum foil current collector and hot-rolled to obtain a double-sided dry negative electrode sheet. S3. The single-sided dry-process positive electrode sheet is immersed in a sodium salt organic solution for pre-sodiumization treatment, then removed and dried to obtain a pre-sodiumized single-sided dry-process positive electrode sheet. S4. Following the uniform orientation and arrangement rules inside the cell, pre-sodium-treated single-sided dry-process positive electrode sheet, separator, and double-sided dry-process negative electrode sheet are stacked layer by layer. After hot pressing and shaping, the sodium-ion battery oriented stacked cell adapted to the single-sided dry-process positive electrode is obtained.

[0016] Preferably, the high-speed shearing process has a rotation speed of 2000~8000 rpm and a time of 5~30 min; the hot roller pressing composite has a temperature of 120~180℃ and a pressure of 2~10 MPa.

[0017] Preferably, the pre-sodium treatment is carried out at a temperature of 50-100°C for 2-12 hours; the sodium salt is one or more of sodium hexafluorophosphate, sodium perchlorate, and sodium difluorosulfonamide; the concentration of the sodium salt is 0.5-2.0 mol / L; and the organic solvent is at least one of ethylene carbonate, diethyl carbonate, and dimethyl carbonate.

[0018] A third aspect of the present invention provides a sodium-ion full battery comprising the above-described sodium-ion battery oriented stacked cell adapted to a single-sided dry cathode.

[0019] The technical solution of the present invention has the following beneficial effects: The sodium-ion battery oriented stacked cell provided by this invention is directly compatible with the current mature single-sided dry cathode process for mass production. Moreover, the stacking arrangement rules are fully compatible with existing stacking tooling, welding, and packaging equipment. No equipment modification is required, and batch sample preparation and performance verification can be quickly achieved, reducing R&D and mass production costs.

[0020] Furthermore, the single-sided dry-process positive electrode of the present invention has a multi-layered gradient dry-process positive electrode active layer. The bottom layer membrane near the current collector has high activity and low porosity, ensuring electrode conductivity and structural stability; the surface layer membrane away from the current collector has low activity and high porosity, optimizing electrolyte wettability and sodium ion transport rate. The gradient pore structure achieves synergistic optimization of electronic conductivity and ion migration, balancing battery cycle stability and coulombic efficiency.

[0021] Furthermore, the present invention adopts a directional arrangement design with the positive electrode facing in a uniform direction, so that the bare aluminum foil surface only has physical contact with the separator, completely cutting off the corrosion reaction pathway between the aluminum foil and the negative electrode active layer and electrolyte, avoiding the generation of high-resistivity products, effectively suppressing the increase of cell internal resistance and capacity decay, and effectively reducing the risk of micro short circuits.

[0022] Furthermore, this invention pre-sodiumizes the positive electrode to embed sodium ions in advance, thereby compensating for the deficiency of sodium ions at the dry electrode interface, reducing the battery's first-cycle impedance, and improving the first coulombic efficiency.

[0023] Meanwhile, unlike existing symmetrical single-sided electrode stacking schemes, this invention is adapted to asymmetric process scenarios where the positive electrode is coated with a single-sided dry coating and the negative electrode is coated with a double-sided coating. It aligns with the current actual production capacity of sodium-ion dry electrodes, resolving a long-standing technical compatibility issue in the industry. Furthermore, the redundant coating on the double-sided negative electrode can compensate for irreversible capacity loss during the first cycle and serves as a sodium replenishment reserve during long-term cycling, effectively mitigating sodium ion loss and improving battery cycle life. Both the positive and negative electrodes of the sodium-ion system use aluminum foil current collectors, simplifying material management and reducing the difficulty of cell recycling.

[0024] Experiments have confirmed that the sodium-ion battery oriented stacked cell of the present invention and the sodium-ion full cell prepared therefrom show significant improvements over existing solutions in terms of aluminum corrosion degree, cycle capacity retention rate, DC internal resistance growth rate, and short-circuit rate. Furthermore, the present invention can achieve full cell assembly of single-sided dry-process sodium-ion cathodes using existing stacking tooling, making it suitable for the research, verification, and large-scale production of sodium-ion batteries, and possessing good industrial practicality and promising prospects for widespread application. Detailed Implementation

[0025] To make the technical solutions and advantages of the present invention clearer, the present invention will be clearly and completely described below in conjunction with specific embodiments. Without departing from the scope or spirit of the present invention, those skilled in the art can make various improvements and changes to the specific embodiments of the present invention, which will be obvious to those skilled in the art.

[0026] Unless otherwise specified, all raw materials used in the following examples are commercially available. Sodium iron pyrophosphate (NFPP) was sourced from Xingrong Xinyuan Technology Co., Ltd., and polytetrafluoroethylene (PTFE) was sourced from Daikin Industries, Ltd.

[0027] Example 1 This embodiment provides a sodium-ion battery oriented stacked cell adapted to a single-sided dry-process positive electrode and a sodium-ion full cell. The sodium-ion battery oriented stacked cell includes alternately stacked positive and negative electrode sheets (5 positive and 4 negative), and a separator disposed between adjacent positive and negative electrode sheets; the positive electrode sheet is a single-sided dry-process positive electrode sheet; the negative electrode sheet is a double-sided dry-process negative electrode sheet; the single-sided dry-process positive electrode sheet includes an aluminum foil current collector; one side of the aluminum foil current collector has a multi-layer gradient dry-process positive electrode active layer, and the other side is an exposed aluminum foil surface; the multi-layer gradient dry-process positive electrode active layer consists of a first positive electrode film layer, a second positive electrode film layer, and a third positive electrode film layer stacked sequentially along the direction away from the aluminum foil current collector, forming a gradient structure with progressively increasing porosity and progressively decreasing active material content.

[0028] The sodium-ion battery oriented stacked cell and sodium-ion full cell of this embodiment are prepared by a method including the following steps: Step 1: Preparation of Single-Sided Dry Cathode Sheet Sodium iron pyrophosphate (NFPP), conductive carbon black, and polytetrafluoroethylene (PTFE) were mixed at a mass ratio of 96:2:2 and dry-stirred at 500 rpm for 30 min to obtain a first dry powder mixture. The first dry powder mixture was then subjected to high-speed shearing at 5000 rpm for 10 min to fibrousize the mixture into a three-dimensional mesh structure, yielding a first fibrous powder. This first fibrous powder was then subjected to a first roll forming process at 80℃ and 15 MPa to obtain a first positive electrode film layer with a thickness of 30 μm and a porosity of 20%.

[0029] Sodium iron pyrophosphate (NFPP), conductive carbon black, and polytetrafluoroethylene (PTFE) were mixed at a mass ratio of 92:4:4 and dry-stirred at 500 rpm for 30 min to obtain a second dry powder mixture. The second dry powder mixture was then subjected to high-speed shearing at 5000 rpm for 10 min to fibrousize the mixture into a three-dimensional mesh structure, yielding a second fibrous powder. This second fibrous powder was then deposited on the surface of the first positive electrode membrane layer, and a second roll forming process was performed at 100℃ and 10 MPa to obtain a second positive electrode membrane layer with a thickness of 40 μm and a porosity of 30%.

[0030] Sodium iron pyrophosphate (NFPP), conductive carbon black, and polytetrafluoroethylene (PTFE) were mixed at a mass ratio of 88:6:6 and dry-stirred at 500 rpm for 30 min to obtain a third dry powder mixture. This third dry powder mixture was then subjected to high-speed shearing at 5000 rpm for 10 min to induce fibrosis and form a three-dimensional mesh structure, yielding a third fibrous powder. This third fibrous powder was then deposited on the surface of the second positive electrode membrane layer and subjected to a third roll forming process at 120℃ and 8 MPa to obtain a third positive electrode membrane layer with a thickness of 20 μm and a porosity of 42%. This resulted in a composite positive electrode membrane with a total thickness of 90 μm and a three-layer gradient structure.

[0031] The composite positive electrode film obtained above was hot-rolled with one surface of an aluminum foil current collector (12 μm thick) at 150°C and 3 MPa, controlling the thickness compression rate of the composite film to be 10% (i.e., the thickness after compression is 90% of the original thickness), so that the areal density of the composite positive electrode film is 15 mg / cm³. 2 It is then firmly bonded to aluminum foil and cut to obtain a single-sided dry-process positive electrode sheet with a peel strength of 28 N / m.

[0032] Step 2: Preparation of double-sided dry negative electrode sheet Hard carbon, conductive carbon black, and polytetrafluoroethylene (PTFE) were mixed at a mass ratio of 92:4:4 and dry-stirred at 500 rpm for 30 min to obtain a negative electrode dry powder mixture. The negative electrode dry powder mixture was then subjected to high-speed shearing at 5000 rpm for 10 min to fibrousize the mixture into a three-dimensional mesh structure, thus obtaining a negative electrode fibrous material.

[0033] The negative electrode fibrous material was roll-pressed at 80℃ and 12MPa to obtain a negative electrode film layer with a thickness of 100μm and a porosity of 35%. Two negative electrode film layers were taken and bonded to both sides of an aluminum foil current collector (12μm thick), respectively. Double-sided hot roll-pressing was then performed at 120℃ and 3MPa, controlling the areal density of the negative electrode film on each side to be 10mg / cm³. 2 This process ensures that the negative electrode film layers on both sides are firmly bonded to the aluminum foil, and then the film is cut to obtain a double-sided dry negative electrode sheet.

[0034] Step 3: Pre-sodiumization treatment The single-sided dry-process positive electrode sheet prepared above was immersed in a composite solution of ethylene carbonate / diethyl carbonate containing 1 mol / L sodium hexafluorophosphate (volume ratio 1:1) and treated at 80°C for 4 hours to pre-intercalate sodium ions into the dry-process positive electrode sheet. After removal, it was dried at 60°C for 2 hours to complete the pre-sodiumization process and obtain a pre-sodiumized single-sided dry-process positive electrode sheet.

[0035] Step 4: Stacking and Assembly In a dry environment with a dew point ≤ -40°C, take a pre-sodium-treated single-sided dry-process positive electrode, a double-sided dry-process negative electrode, and a separator (polyethylene separator), and stack them sequentially on a stacking table according to the following orientation arrangement rules: place the pre-sodium-treated single-sided dry-process positive electrode (coated side up), separator, double-sided dry-process negative electrode, separator, and pre-sodium-treated single-sided dry-process positive electrode (coated side down) in sequence to form a basic stacking unit of 2 positive and 1 negative electrode. Then repeat this unit to form a stacked core with a target layer count of 5 positive and 4 negative electrodes, which is the sodium-ion battery oriented stacked cell of this embodiment.

[0036] During the aforementioned lamination process, a limiting fixture is used to fix the position of the electrode sheets, ensuring that the coatings of all positive electrode sheets face the same direction and preventing accidental contact between the bare aluminum of the positive electrode sheet and the negative electrode active layer due to lamination misalignment. Specifically, the arrangement cycle of the basic lamination unit is as follows: exposed aluminum foil surface - multi-layer gradient dry positive electrode active layer || separator || negative electrode active layer - aluminum foil - negative electrode active layer || separator || multi-layer gradient dry positive electrode active layer - exposed aluminum foil surface.

[0037] After stacking, the sodium-ion full cell of this embodiment is obtained by hot pressing (temperature 80°C, pressure 0.5MPa), encapsulation, and injection of sodium electrolyte (1.0M NaPF6 PC solution with 5 vol% FEC added).

[0038] In one specific embodiment, the aforementioned limiting fixture is implemented as follows: Four corner positioning areas (positioning posts or positioning grooves) are set on the stacking table. The electrode is placed within the positioning area, and the size of the positioning area is 0.1~0.3mm larger than the electrode size to ensure that the electrode does not undergo displacement greater than this gap during stacking. For each layer stacked, vacuum adsorption is used to temporarily fix the electrode position until stacking is complete. For pouch cells, the length and width dimensional errors of the electrode must be controlled within ±0.2mm to ensure that the positive electrode coating area completely falls within the negative electrode coating area, thereby preventing sodium deposition.

[0039] In other embodiments, the target number of layers in the stacked core package can be set to other numbers as needed, such as 10 positive and 9 negative, 12 positive and 11 negative, etc. The present invention does not impose any special restrictions on it, as long as the number of positive electrode sheets is always one more than the number of negative electrode sheets.

[0040] In other embodiments, the separator and sodium electrolyte may be made of other battery-grade materials, which can be conventionally selected by a technician.

[0041] Example 2 This embodiment provides a sodium-ion battery oriented stacked cell adapted to a single-sided dry-process cathode and a sodium-ion full cell. The preparation method is basically the same as in Embodiment 1, the difference being the different three-layer gradient pore structure parameters of the dry-process cathode film. In step one of this embodiment, the first cathode film layer has a thickness of 25 μm, a porosity of 18%, and a mass ratio of NFPP, conductive carbon black, and PTFE of 95:2.5:2.5; the second cathode film layer has a thickness of 35 μm, a porosity of 28%, and a mass ratio of NFPP, conductive carbon black, and PTFE of 92:4:4; the third cathode film layer has a thickness of 15 μm, a porosity of 45%, and a mass ratio of NFPP, conductive carbon black, and PTFE of 89:5.5:5.5. The total thickness of the composite cathode film is 75 μm.

[0042] Example 3 This embodiment provides a sodium-ion battery oriented stacked cell adapted for a single-sided dry cathode and a sodium-ion full cell. The preparation method is basically the same as in Embodiment 1, except for the different pre-sodiuming process parameters. In step three of this embodiment, the pre-sodiuming conditions are as follows: the pre-sodiuming solvent is a composite solution of ethylene carbonate / dimethyl carbonate (volume ratio 1:1) containing 1.5 mol / L sodium bis(fluorosulfonyl)imide, and the solution is impregnated at 60°C for 8 hours.

[0043] Comparative Example 1 This comparative example provides a sodium-ion battery stacked cell and a sodium-ion full cell, whose preparation method is basically the same as that of Example 1, except that the dry-process positive electrode film does not contain the gradient structure of Example 1, but is a single-layer uniform porous structure. Specifically, in step one, the preparation process of the single-sided dry-process positive electrode sheet is adjusted as follows: according to the preparation process of the second positive electrode film layer in Example 1, a positive electrode film layer with a thickness of 40 μm and a porosity of 30% is prepared. The positive electrode film layer is then hot-rolled according to the process of Example 1 to obtain a single-sided dry-process positive electrode sheet, and the remaining processes are the same as in Example 1.

[0044] Comparative Example 2 This comparative example provides a sodium-ion battery stacked cell and a sodium-ion full cell. The preparation method is basically the same as that of Example 1. The difference is that in step one, the composite positive electrode film is a two-layer gradient structure. That is, the preparation of the second positive electrode film layer is omitted, and only the first positive electrode film layer and the third positive electrode film layer are prepared, thereby obtaining a composite positive electrode film with a two-layer gradient structure. The rest of the process is the same as that of Example 1.

[0045] Comparative Example 3 This comparative example provides a sodium-ion battery stacked cell and a sodium-ion full cell. The preparation method is basically the same as that of Example 1, except that the pre-sodium treatment is not performed, that is, step three in Example 1 is omitted, and the rest of the process is the same as that of Example 1.

[0046] Comparative Example 4 This comparative example provides a sodium-ion battery stacked cell and a sodium-ion full cell, the preparation method of which is basically the same as that of Example 1, the difference being the stacking process in step three. In this comparative example, the coating orientation of the single-sided dry-process positive electrode sheet is randomly arranged during stacking, with some facing upwards and some facing downwards, without a uniform orientation rule. In actual stacking, the positive electrode sheet coating is arranged sequentially downwards, upwards, upwards, downwards, and upwards.

[0047] Test case The following tests were conducted on the performance of the sodium-ion full cells prepared in Examples 1-3 and Comparative Examples 1-4 of this invention. The test indicators include: Initial coulombic efficiency: At 25±1℃, the sodium-ion full cell was charged at a constant current of 0.05C to 4.2V, and then charged at a constant voltage until the current dropped to 0.01C. The initial charge specific capacity was recorded. Subsequently, it was discharged at a constant current of 0.05C to 2.5V, and the initial discharge specific capacity was recorded. Initial coulombic efficiency (%) = (initial discharge specific capacity / initial charge specific capacity) × 100%.

[0048] 500-cycle capacity retention: After the sodium-ion battery was placed in a constant temperature chamber at 25±1℃ for 12 hours, a constant current charge-discharge cycle test was performed at a current density of 1C / 1C, with a voltage range of 2.5V~4.2V. The battery was rested for 5 minutes between charge and discharge cycles. The ratio of the discharge capacity in the 500th cycle to the discharge capacity in the 1st cycle was recorded. That is, the 500-cycle capacity retention (%) = (discharge capacity in the 500th cycle / discharge capacity in the 1st cycle) × 100%.

[0049] DC internal resistance (DCR) growth rate: At 25±1℃, the battery was adjusted to 50% state of charge and discharged at a 0.1C current for 30 seconds. The voltage difference ΔV and current difference ΔI before and after discharge were recorded. The initial DC internal resistance value was calculated according to DCR (mΩ) = ΔV / ΔI. Following the above method, the DC internal resistance value was measured after the 500th cycle test, and the DCR growth rate was calculated. The DCR growth rate (%) = (DCR value after 500 cycles / Initial DCR value - 1) × 100%.

[0050] Corrosion area: After 500 cycles of testing, the battery was disassembled at 25±1℃, the positive electrode was removed, the positive electrode active layer was peeled off and washed with deionized water and dried. The surface of the positive electrode current collector was photographed under an optical microscope and the percentage (%) of the corrosion area to the total positive electrode area was calculated using image analysis software.

[0051] Short circuit rate: The number of sodium-ion batteries that experience micro-short circuits or hard short circuits after the formation process is statistically analyzed. The short circuit rate is calculated using the following formula: Short circuit rate = (Number of short-circuited batteries / Total number of batteries) × 100%.

[0052] Table 1 shows the performance test results of the sodium-ion full cells prepared in Examples 1-3 and Comparative Examples 1-4.

[0053] Table 1. Performance test results of sodium-ion full batteries

[0054] As shown in Table 1, the sodium-ion full cells prepared in Examples 1-3 of this invention exhibit significant improvements over Comparative Examples 1-4 in terms of aluminum corrosion degree, cycle capacity retention, DCR growth rate, and short-circuit rate, with Example 1 showing the best performance. Furthermore, Comparative Example 1 did not employ a gradient structure, and Comparative Example 2 employed only a two-layer gradient structure; its initial efficiency, capacity retention, and DCR growth rate were significantly inferior to Example 1. This demonstrates that the three-layer gradient structure, through its progressively increasing porosity design, can effectively improve electrolyte wetting and buffer volume change stress, thereby enhancing cycle stability and reducing impedance growth. Comparative Example 3, without pre-sodiumization treatment, had an initial efficiency of only 82.6%, 6% lower than Example 1. This proves that pre-sodiumization is a key step in improving initial efficiency, compensating for the sodium consumption required for the formation of the SEI film in the first cycle by pre-embedding sodium ions. Comparative Example 4, which did not employ directional stacking (coating orientation was random), had a significantly higher corrosion area (5.8%) and short-circuit rate (3.6%) than Example 1. It also exhibited the lowest 500-cycle capacity retention (88.3%) and the highest DCR growth rate (38.5%). This demonstrates that the directional stacking process, by ensuring consistent coating orientation and precise alignment, can effectively prevent accidental contact between bare aluminum and the negative electrode active layer, thereby significantly improving battery safety and cycle life.

[0055] In summary, this invention achieves a comprehensive improvement in the overall performance of sodium-ion full cells through the synergistic effect of a three-layer gradient dry cathode structure, pre-sodiumization treatment, and directional stacking arrangement process. Furthermore, this invention can achieve full cell assembly of single-sided dry sodium cathodes using existing stacking tooling, making it suitable for the research, verification, and large-scale production of sodium-ion batteries, demonstrating good industrial practicality and promising prospects for widespread application.

[0056] The above description is only a preferred embodiment of the present invention. For those skilled in the art, several improvements and modifications can be made without departing from the spirit and principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A sodium-ion battery oriented stacked cell adapted for a single-sided dry-process positive electrode, characterized in that, It includes several alternating positive and negative electrode plates, and a separator disposed between adjacent positive and negative electrode plates; The positive electrode is a single-sided dry-process positive electrode; the negative electrode is a double-sided dry-process negative electrode; the single-sided dry-process positive electrode includes an aluminum foil current collector; one side of the aluminum foil current collector is provided with a multi-layer gradient dry-process positive electrode active layer, and the other side is an exposed aluminum foil surface; the multi-layer gradient dry-process positive electrode active layer is sequentially stacked with a first positive electrode film layer, a second positive electrode film layer, and a third positive electrode film layer along the direction away from the aluminum foil current collector, forming a gradient structure in which the porosity increases layer by layer and the content of active material decreases layer by layer; The first positive electrode membrane layer has a porosity of 15%~25% and a positive electrode active material content of 95%~97%; the second positive electrode membrane layer has a porosity of 25%~35% and a positive electrode active material content of 91%~93%; the third positive electrode membrane layer has a porosity of 35%~50% and a positive electrode active material content of 87%~89%. The positive electrode plates are arranged in a uniform orientation inside the cell, that is, the multi-layer gradient dry positive electrode active layer faces the negative electrode plate, and the exposed aluminum foil faces outward.

2. The sodium-ion battery oriented stacked cell adapted for a single-sided dry-process positive electrode according to claim 1, characterized in that, The total thickness of the multilayer gradient dry positive electrode active layer is 60~140μm; the thickness of the first positive electrode film layer is 20~50μm; the thickness of the second positive electrode film layer is 30~60μm; and the thickness of the third positive electrode film layer is 10~30μm.

3. The sodium-ion battery oriented stacked cell adapted for a single-sided dry-process positive electrode according to claim 1, characterized in that, The positive active material in the multilayer gradient dry positive electrode active layer is at least one of sodium iron pyrophosphate, Prussian blue analogue, and layered oxide.

4. The sodium-ion battery oriented stacked cell adapted for a single-sided dry-process positive electrode according to claim 1, characterized in that, The double-sided dry negative electrode sheet includes an aluminum foil current collector and negative electrode active layers disposed on both sides of the aluminum foil current collector; the negative electrode active material in the negative electrode active layer is hard carbon; the double-sided dry negative electrode sheet only has the negative electrode active layer on the side facing the multilayer gradient dry positive electrode active layer participating in the electrochemical reaction, and the negative electrode active layer on the other side is a capacity redundancy sodium replenishment reserve layer.

5. The sodium-ion battery oriented stacked cell adapted for a single-sided dry-process positive electrode according to claim 1, characterized in that, The directional arrangement cycle unit of the sodium-ion battery directional stacked cell is: exposed aluminum foil surface - multi-layer gradient dry positive electrode active layer || separator || negative electrode active layer - aluminum foil - negative electrode active layer || separator || multi-layer gradient dry positive electrode active layer - exposed aluminum foil surface; the number of positive electrode sheets is 1 more than the number of negative electrode sheets.

6. The sodium-ion battery oriented stacked cell adapted for a single-sided dry-process positive electrode according to any one of claims 1 to 5, characterized in that, The single-sided dry-process positive electrode sheet undergoes pre-sodium treatment.

7. A method for preparing a sodium-ion battery oriented stacked cell adapted to a single-sided dry-process cathode, used to prepare a sodium-ion battery oriented stacked cell according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1. The positive electrode active material, conductive agent, and polytetrafluoroethylene are dry-mixed at a mass ratio of 86~97:1.5~10:1.5~10, and then subjected to high-speed shearing to obtain positive electrode fibrous powders with different proportions. The fibrous powders with different proportions are taken in batches and layered by roller pressing to prepare the first positive electrode film layer, the second positive electrode film layer, and the third positive electrode film layer in sequence, forming a gradient dry positive electrode film. The gradient dry positive electrode film is placed on one side of the aluminum foil current collector and then hot-rolled to obtain a single-sided dry positive electrode sheet. S2. The negative electrode active material, conductive agent, and polytetrafluoroethylene are dry-mixed according to the mass ratio, and then subjected to high-speed shearing to obtain negative electrode fibrous powder; the negative electrode fibrous powder is rolled to obtain a negative electrode film layer; the negative electrode film layer is attached to both sides of the aluminum foil current collector and hot-rolled to obtain a double-sided dry negative electrode sheet. S3. The single-sided dry-process positive electrode sheet is immersed in a sodium salt organic solution for pre-sodium treatment, then removed and dried to obtain a pre-sodium-treated single-sided dry-process positive electrode sheet. S4. Following the uniform orientation and arrangement rules inside the cell, pre-sodium-treated single-sided dry-process positive electrode sheet, separator, and double-sided dry-process negative electrode sheet are stacked layer by layer. After hot pressing and shaping, the sodium-ion battery oriented stacked cell adapted to the single-sided dry-process positive electrode is obtained.

8. The method for preparing a sodium-ion battery oriented stacked cell adapted to a single-sided dry-process cathode according to claim 7, characterized in that, The high-speed shearing process is performed at a speed of 2000~8000 rpm for 5~30 min; the hot roller pressing process is performed at a temperature of 120~180℃ and a pressure of 2~10 MPa.

9. The method for preparing a sodium-ion battery oriented stacked cell adapted to a single-sided dry-process cathode according to claim 7, characterized in that, The pre-sodium treatment is carried out at a temperature of 50-100℃ for 2-12 hours; the sodium salt is one or more of sodium hexafluorophosphate, sodium perchlorate, and sodium difluorosulfonamide; the concentration of the sodium salt is 0.5-2.0 mol / L; and the organic solvent is at least one of ethylene carbonate, diethyl carbonate, and dimethyl carbonate.

10. A sodium-ion full battery, characterized in that, A sodium-ion battery oriented stacked cell with an adapted single-sided dry cathode as described in any one of claims 1 to 6.